2015
DOI: 10.1007/s00221-015-4427-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hand kinematics reveals inter-individual differences in intertemporal decision dynamics

Abstract: During intertemporal decisions, the preference for smaller, sooner reward over larger-delayed rewards (temporal discounting, TD) exhibits substantial inter-subject variability; however, it is currently unclear what are the mechanisms underlying this apparently idiosyncratic behavior. To answer this question, here we recorded and analyzed mouse movement kinematics during intertemporal choices in a large sample of participants (N = 86). Results revealed a specific pattern of decision dynamics associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 53 publications
6
37
0
Order By: Relevance
“…In order to exemplify this conclusion in the case of intertemporal choice, we refer to the literature that also investigated the action dynamics of intertemporal decision making. To our knowledge there exist only four studies including our original work (Calluso et al, 2015;Dshemuchadse et al, 2013;O'Hora et al, 2016;Scherbaum et al, 2018a). The most basic results of those studies focused on the comparison of mouse movements between choices of the soonsmall and the late-large option.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to exemplify this conclusion in the case of intertemporal choice, we refer to the literature that also investigated the action dynamics of intertemporal decision making. To our knowledge there exist only four studies including our original work (Calluso et al, 2015;Dshemuchadse et al, 2013;O'Hora et al, 2016;Scherbaum et al, 2018a). The most basic results of those studies focused on the comparison of mouse movements between choices of the soonsmall and the late-large option.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in the last ten years, mouse-tracking flourished in many fields of psychological research (for a review, see Erb, 2018;Freeman, 2018;Freeman, Dale, & Farmer, 2011), finding applications in studies of phonological and semantic processing (Dale et al, 2007;Dshemuchadse, Grage, & Scherbaum, 2015;Spivey et al, 2005), cognitive control (Dignath, Pfister, Eder, Kiesel, & Kunde, 2014;Scherbaum, Dshemuchadse, Fischer, & Goschke, 2010;Yamamoto, Incera, & McLennan, 2016), selective attention (Frisch, Dshemuchadse, Görner, Goschke, & Scherbaum, 2015), numerical cognition (Szaszi, Palfi, Szollosi, Kieslich, & Aczel, 2018), perceptual choices (Quinton, Volpi, Barca, & Pezzulo, 2014), moral decisions (Koop, 2013), preferential choices (Koop & Johnson, 2013;O'Hora, Dale, Piiroinen, & Connolly, 2013), lexical decisions (Barca & Pezzulo, 2012, 2015, and value-based decisions (Calluso, Committeri, Pezzulo, Lepora, & Tosoni, 2015;Dshemuchadse et al, 2013;Kieslich & Hilbig, 2014;Koop & Johnson, 2011;O'Hora, Carey, Kervick, Crowley, & Dabrowski, 2016;Scherbaum et al, 2016;Scherbaum, Dshemuchadse, Leiberg, & Goschke, 2013;Scherbaum, Frisch, & Dshemuchadse, 2018b, 2018avan Rooij, Favela, Malone, & Richardson, 2013).…”
Section: Mouse-tracking As a Process-tracing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast with the findings of Dshemuchadse et al (2013), who identified a bias towards the SS option in mouse cursor trajectories. To further complicate the issue, Calluso et al (2015) and O'Hora et al (2016) found a bias in the opposite direction, towards the LL option.…”
Section: Symmetrically Increased Motor Costs Of Responding Do Not Affmentioning
confidence: 99%
“…On the basis of this assumption, this new method has been applied in nearly all aspects of cognitive and social decision making studies, including delay discounting and stop-signal tasks (Dschemuchadse et al, 2013, O'Hora et al, 2016, numerical judgment (Xiao & Yamauchi, 2015), categorization (Dale, Kehoe, & Spivey, 2007), inductive reasoning (Yamauchi, Kohn, & Yu, 2007), linguistic judgment (Spivey, Grosjean, & Knoblich, 2005), racial and gender judgment of morphed face pictures Freeman, Pauker, Apfelbaum, & Ambady, 2009), attitudinal ambivalence toward certain topics (e.g., abortion) (Schneider et al, 2015;Wojnowicz, Ferguson, Dale, & Spivey, 2009), uncertainty in economic choices (Calluso, Committeri, Pezzulo, Lepora, & Tosoni, 2015), and among others (see for review , Freeman, 2018;Stillman et al, 2018;Yamauchi, Leontyev, & Wolfe, 2017).…”
Section: Figure 1 Comparison Between Keypress (Upper Panel) and Mousmentioning
confidence: 99%